2019
DOI: 10.1159/000503751
|View full text |Cite
|
Sign up to set email alerts
|

Examining Weight Bias among Practicing Canadian Family Physicians

Abstract: <b><i>Objectives:</i></b> The aim of this study was to examine the attitudes of practicing Canadian family physicians about individuals with obesity, their healthcare treatment, and perceptions of obesity treatment in the public healthcare system. <b><i>Method:</i></b> A national sample of Canadian practicing family physicians (<i>n</i> = 400) completed the survey. Participants completed measures of explicit weight bias, attitudes towards treating pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
3
27
0
1
Order By: Relevance
“…Here, most doctors expressed the feeling that they are not making any difference in getting their patients to make long-term lifestyle changes; they tend to blame obese patients as unmotivated and not-compliant, very similar to the first type in the present study (the resigned). A Canadian survey of 400 general practitioners comes to similar results [18]. Another commonality between the present study and the work of Teixeira et al [17] is that GPs feel left alone to a certain extent when caring for obese patients; the desire for more referral options is expressed.…”
Section: Comparison With Prior Worksupporting
confidence: 84%
See 2 more Smart Citations
“…Here, most doctors expressed the feeling that they are not making any difference in getting their patients to make long-term lifestyle changes; they tend to blame obese patients as unmotivated and not-compliant, very similar to the first type in the present study (the resigned). A Canadian survey of 400 general practitioners comes to similar results [18]. Another commonality between the present study and the work of Teixeira et al [17] is that GPs feel left alone to a certain extent when caring for obese patients; the desire for more referral options is expressed.…”
Section: Comparison With Prior Worksupporting
confidence: 84%
“…Previous studies have already noted that general practitioners are often reticent in taking a proactive role in obesity management as they perceive a lack of patient motivation as a serious hindrance [ 21 ]. In some cases, pronounced stereotypes and stigmatisations can be observed on the part of doctors [ 15 , 16 , 18 ]. The present study results point to the work of Teixeira and colleagues, in which the attitudes of Portuguese GPs to obesity management were examined [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight bias and stigmatization of patients with obesity in healthcare is common and well-documented [16]. There is a considerable volume of research and data that indicate that healthcare is rife with weight bias, stigmatization, prejudice, and discrimination and that biased attitudes and behaviors negatively affect the delivery and quality of care for patients with obesity.…”
Section: Healthcarementioning
confidence: 99%
“…[23][24][25] In a sample of family physicians practising in Canada (n = 400), large proportions gave responses suggestive of weight bias: 49% agreed that "people with obesity increase demand on the public health care system"; 33% stated they "often feel frustrated with patients who have obesity"; 28% stated they felt "patients with obesity are often noncompliant with treatment recommendations"; 19% said "I feel disgust when treating a patient with obesity"; and 17% indicated that "sometimes I think that people with obesity are dishonest." 26 Under-explored in Canada is the prevalence of weight-based stigma in different settings, despite its pernicious effects. 27 This study aims to address this knowledge gap by assessing the association of higher body weight with self-reported discrimination in health care among Canadian women and men.…”
Section: Introductionmentioning
confidence: 99%